Essays in Labour History, in Memory of G.D.H. Cole - Jean-Réal Cardin (Relations industrielles / Industrial Relations, 1961)
The article reviews the book, "Essays in Labour History, in Memory of G.D.H. Cole," edited by Asa Briggs and John Saville, with recollections of G.D.H. Cole by Ivor Brown, Hugh Gaitskell, Stephen K. Bailey and G.N.D. Worswick.